Green approach to treat institutional wastewater by using cassava peels starch (CPS) as coagulant aid - Kumar, Vicky (2018)
The quality of water is superior for the stability of the ecosystem. Institutional wastewater contains pollutants and exceed the level of contaminants beyond standards. Applications of natural coagulants are widely in practice due to abundant source, low price, environment-friendly and rapid biodegradable as compared to inorganic based coagulants. This study traces the potential removal of pollutants from institutional wastewater by coagulation-flocculation processes. Alum as primary coagulant and CPS as coagulant aid was used for removal of pollutants. A series of batch experiments were performed to study the removal mechanism to achieve optimum pH, dosage, and settling time, to premeditated institutional wastewater removal efficiency (%) of COD, TSS & Turbidity. Institutional wastewater physicochemical characteristics were analyzed by pH, temperature, turbidity, COD, TSS, BOD, Characteristics of CPS were characterized by SEM-EDX, FTIR, XRF, XRD, particle size and zeta potential. Removal efficiency of dual coagulant (alum+CPS) were achieved at optimum dosage of 40:60 mg/L at pH 8 with 60 mins settling time with removal efficiency of COD (41%), TSS (86%) and Turbidity (91%). Selected parameters study showed a significant reduction (P<0.05) for wastewater treatment. After coagulation and flocculation process, produced sludge was further characterized with SEM-EDX, FTIR and Zeta potential. However, zeta potential results revealed that stability of alum+CPS at pH 8 were proven in removal efficiency and mechanism study. Due to high removal achieved in the reduction of pollutants, therefore, the CPS as coagulant aid has potential for the treatment of institutional wastewater.